General Anesthesia for Patients With Chronic Obstructive Pulmonary Disease and Postoperative Respiratory Failure: A Retrospective Analysis of 120 Patients - Hou, Ruixue; Miao, Fangfang; Jin, Di; Duan, Qingfang; Yin, Cheng; Feng, Qunpeng; Wang, Tianlong (Frontiers in Physiology, 2022)
Background: Chronic obstructive pulmonary disease (COPD) has been considered a risk factor for postoperative respiratory failure after general anesthesia. However, the association between COPD severity and postoperative respiratory failure among COPD patients is unknown. Our aim was to compare the prevalence of postoperative respiratory failure in COPD patients according to disease severity after general anesthesia. Methods: We retrospectively reviewed CDPD patients undergoing spinal surgery with general anesthesia at our clinical center between January 2016 and January 2021. These subjects were divided into four groups according to their preoperative lung function. The primary endpoint was respiratory failure at 1 week after surgery. The diagnosis of respiratory failure was made with the presence of one or more of the following criteria: prolonged ventilator dependence, unplanned postoperative intubation, room air PaO2 ≤ 50mmHg in arterial blood gas samples. The extubation time, PaO2 and PaCO2 perioperatively, postoperative lung infection, and length of hospitalization were also compared. Results: A total of 120 patients who underwent spinal surgery with general anesthesia were included in this retrospective study. Postoperative respiratory failure occurred in 0 (0.0%) patient in Group I, 1 (1.5%) patient in Group II, 1 (2.5%) patient in Group III, 1 (14.5%) patient in Group IV at 1 week after surgery (p = 0.219). The univariate analysis revealed that preoperative higher PaO2 was associated with lower rate of postoperative respiratory failure (OR 0.83; 95%CI, 0.72 to 0.95; p = 0.007). The time of anesthesia was 243.3 ± 104.3 min in Group I, 235.5 ± 78.8 min in Group II, 196.0 ± 66.3 min in Group III and 173.1 ± 63.7 min in Group IV, respectively (p < 0.001). Preoperative PaO2, PaCO2, intraoperative FiO2 and postoperative PaO2 were significantly different among the four groups (p < 0.001, 0.001, 0.046, < 0.001, respectively). No statistic differences among the four groups were seen in extubation time, pulmonary infection and hospital stays (p = 0.174, 0.843, 0.253, respectively). Conclusions: Patients with different severe COPD defined as FEV1%pred were not related to postoperative respiratory failure. However, preoperative lower PaO2 was associated with greater odds of postoperative respiratory failure in COPD patients.